Official Intervention in the Foreign Exchange Market : Elements of Best Practice - Canales Kriljenko, Jorge; Guimaraes, Roberto; Karacadag, Cem. (Washington, D.C. : International Monetary Fund, 2003)
This paper offers guidance on the operational aspects of official intervention in the foreign exchange market, particularly in developing countries with flexible exchange rate regimes. A brief survey of the literature and country experience is followed by an analysis of the objectives, timing, amount, degree of transparency, and choice of markets and counterparties in conducting intervention. The analysis highlights the difficulty of detecting exchange rate misalignments and disorderly markets, and argues in favor of parsimony in official intervention. Determining the timing and amount of intervention is a highly subjective excercise, and some degree of discretion is almost necessary, though policy rules may serve as "rules of thumb.".
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet